Effects of different chemical modifiers on the determination of arsenic by electrothermal atomic absorption spectrometry and application to the poultry and plant samples - Yaman, M.; Akdeniz, I. (Dustri-Verlag Dr Karl Feistle, 2006)
Selected mixed modifiers were examined for the determination of arsenic by platform atomization-ETAAS. These matrix modifiers include the nitrate salts of palladium and the mixtures of calcium, magnesium, iron, molybdenum and nickel and triton-X 100. The palladium and the mixture of Ca + Mg + Triton X-100 were found to be the best reagents as modifier in comparison with the other studied modifiers. The optimized method was applied to the determination of As in poultry samples such as egg and chicken meat and chicken feed and plants such as grass, clover and pine leaves taken from east of Turkey. Approximately, 3.5-fold higher As concentration in egg white than in egg yolk was found. The other obtained data were compared to the literature values.
Keywords: chemical modifier; GFAAS; arsenic; egg; chicken; poultry; plant